Pengumpulan Dan Penulisan Al-Quran Serta Implikasinya Pada Pendidikan Islam - Khofifaturrochmah; Muhammad Alfiansyah; Dedi Masri; Ana Hijrah Nst; Rizky Syaifaturrahman (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2023)
This study aims to find out more about the writing and collection of the Koran and its implications for Islamic education. This study uses the library research method (literature study) where the author in working on the journal looks, searches and collects data with books, journals, articles, and anything related to the title and after collecting the data obtained, the writer uses the method of analysis (content analysis). The results of this study indicate that the positions of the Koran and hadith in Islamic education have similarities between the two, namely that they are the main references in Islamic education, but both also have differences. And the implications of the Koran for Islamic educatin cannot be separated, because the beginning of the knowledge taught to the Prophet was the Koran (Q.S al-alaq verses 1-5).